2010
DOI: 10.1097/aap.0b013e3181c7717c
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Comparison Between Single- and Double-Injection Ultrasound-Guided Infraclavicular Brachial Plexus Block

Abstract: The double-injection ultrasound-guided infraclavicular block provides no significant advantages compared with its single-injection counterpart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 8 publications
1
82
0
7
Order By: Relevance
“…In conclusion, and in accordance with previous work (7,15,16), no significant difference was observed in the success rates of the SI and multiple injection methods. However, the TI method for IBPB resulted in improved onset time and more complete sensory and motor blocks at 10 min compared with the SI method.…”
Section: Discussionsupporting
confidence: 80%
“…In conclusion, and in accordance with previous work (7,15,16), no significant difference was observed in the success rates of the SI and multiple injection methods. However, the TI method for IBPB resulted in improved onset time and more complete sensory and motor blocks at 10 min compared with the SI method.…”
Section: Discussionsupporting
confidence: 80%
“…28 Several clinical studies have confirmed this hypothesis. 20,29 A fascial click is felt just before reaching the posterior aspect of the artery and signals that the needle tip is in the right location. 20 For the technique to be successful, a U-shaped spread posterior to the artery (i.e., the artery being pushed anteriorly by the local anesthetic) should be …”
Section: Infraclavicular Approachmentioning
confidence: 99%
“…Plusieurs études cliniques ont confirmé cette hypothèse. 20,29 Un clic fascial est ressenti juste avant d'arriver en postérieur de l'artère et signe que la pointe de l'aiguille est au bon endroit. 20 Pour un bon succès, dès les premiers millilitres injectés, il faut observer une distribution en U en postérieur de l'artère, qui se fait repousser en antérieur par l'anesthésique local (Figs.…”
Section: Approche Infraclaviculaireunclassified
“…For verifying the position of injection needle about sciatic nerve, the methods of paresthesia search and electric stimulation of peripheral nerves were applied [1]. Use of ultrasound-guided regional anesthesia increases efficiency up to 96% -100% [2][3][4]. With the development of new technologies, new methods of verifying the position of injection needle about a nerve appeared which can evaluate the characteristics of local anesthetic spreading in such kind of peripheral blocks, as stellate ganglion block [5].…”
Section: Introductionmentioning
confidence: 99%